Early Detection of Preeclampsia Using the Dhiana Setyorini Score Card (DSSC) Digital Application in the Working Area of Tamamaung Public Health Center, Makassar - Suriyani Suriyani; Muaningsih Muaningsih; Mikawati Mikawati; Rizky Pratiwi; Evi Lusiana; Natasya Akuba; Nazwa Zulianty Ali (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2026)
Preeclampsia is one of the leading causes of maternal mortality in Indonesia, with hypertensive disorders of pregnancy accounting for the largest proportion of the 4,129 maternal deaths reported in 2023. Early detection at the primary healthcare level remains limited because screening largely depends on healthcare providers, while pregnant women’s knowledge of preeclampsia is still inadequate. This community service program aimed to improve pregnant women’s knowledge of preeclampsia and conduct early risk screening using the Digital Dhiana Setyorini Score Card (DSSC) Application in the working area of Tamamaung Primary Health Center, Makassar, Indonesia. The program was implemented in December 2025 and involved pregnant women attending Posyandu in RW 1–RW 7. Activities included coordination with the Primary Health Center, needs assessment, health education on preeclampsia, and digital risk screening using the KSDS application. Knowledge was evaluated before and after the education session, and screening outcomes were documented. Before the intervention, only 30% of participants had adequate knowledge of preeclampsia, and none had undergone risk screening. After the intervention, 100% demonstrated adequate knowledge. Of the 10 pregnant women screened, 80% were classified as low risk and 20% as high risk. The findings suggest that integrating health education with the KSDS digital application effectively improves knowledge and strengthens early detection of preeclampsia risk at the community level. Routine implementation in primary healthcare settings is recommended.